(untitled) (Journal of Nepal Physical Society, 2024)
In this work, we analyzed variations in the Earth’s magnetic field components (D, H, and Z), interplanetary magnetic field (IMF-Bz), interplanetary electric field (IEF-Ey), and GPS-derived total electron content (TEC) during three solar storms observed over Eagle Station (64.7860°N, 141.1999°W) in Canada during Solar Cycle 24. The selected events include a moderate storm (25–27 October 2011), an intense storm (15–19 March, 2015), and a weak storm (6–10 May, 2018). The results indicate that solar storms caused notable disturbances in all components of the geomagnetic field, with the D, H, and Z components showing marked decreases during storm periods. These disturbances were accompanied by a corresponding increase in TEC. Additionally, the degree of geomagnetic variation was closely linked to the intensity of geomagnetic storms.